New battlefields/old laws critical debates on symmetric warfare - Banks, William C. (Columbia University Press, 2011)
Here, multiple scholars confront the changing nature of conflict and whether the laws of war should equally evolve. The book begins with the premise that many of today's conflicts are low-intensity, asymmetrical wars fought between disparate military forces